Digitalization in anaesthesiology and intensive care – a start for artificial intelligence? - Yu. S. Polushin; I. V. Shlyk; N. S. Smolin; G. A. Timofeev (Вестник анестезиологии и реаниматологии, 2024)
The article presents reflections on the place of digitalization in the development of domestic anesthesiology and intensive care. The important role of this technology in ensuring high-quality treatment is shown. The practical component of implementing tasks within the framework of digitalization should include reducing the workload on personnel not related to direct work with the patient, but also changing the management of treatment system to improve its efficiency and the safety of medical activities.